2006
DOI: 10.1084/jem.20061308
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-22 and IL-17 are coexpressed by Th17 cells and cooperatively enhance expression of antimicrobial peptides

Abstract: Th17 cells are a distinct lineage of effector CD4+ T cells characterized by their production of interleukin (IL)-17. We demonstrate that Th17 cells also expressed IL-22, an IL-10 family member, at substantially higher amounts than T helper (Th)1 or Th2 cells. Similar to IL-17A, IL-22 expression was initiated by transforming growth factor β signaling in the context of IL-6 and other proinflammatory cytokines. The subsequent expansion of IL-22–producing cells was dependent on IL-23. We further demonstrate that I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
1,816
7
15

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,044 publications
(1,932 citation statements)
references
References 19 publications
57
1,816
7
15
Order By: Relevance
“…More recently, it has been argued that Th17 cells are also major producers of IL-22 (12,42). The current view of mouse Th17 development is that TGF␤1 and IL-6 are the key cytokines that initiate the differentiation process and that IL-23 plays an essential role in the expansion and maintenance of this lineage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it has been argued that Th17 cells are also major producers of IL-22 (12,42). The current view of mouse Th17 development is that TGF␤1 and IL-6 are the key cytokines that initiate the differentiation process and that IL-23 plays an essential role in the expansion and maintenance of this lineage.…”
Section: Discussionmentioning
confidence: 99%
“…IL-22 is a member of the IL-10 family, and its gene is located on chromosome 12q15 between the IFN␥ and IL-26 loci (40,41). Recently, IL-22 has been reported to be produced by murine Th17 cells in vitro and in vivo (12,42). We sought to determine whether the expression of IL-22 in human CD4ϩ T cells was regulated in the same manner as that of IL-17A and IL-17F.…”
Section: Il-17 Regulation In Human T Cells 2941mentioning
confidence: 99%
See 1 more Smart Citation
“…IL-22 was first reported to be associated with Th1 cells but was subsequently shown to be secreted by Th17 cells, gdT cells, NKT cells, NK cells, CD11c 1 myeloid cells and lymphoid tissue inducer-like cells [16][17][18][19]. The in vitro differentiation of Th17 cells produces a population of cells with a single expression of IL-17 and IL-22 and the coexpression of IL-17 and IL-22 [16]. Although both IL-6 and TGF-b are necessary for Th17 cell differentiation, IL-6 or IL-23 induces IL-22 production, whereas TGF-b inhibits IL-22 production [4].…”
Section: Introductionmentioning
confidence: 99%
“…Expression analysis has revealed that IL-22 was significantly induced in lymphoid tissues including spleen and intestine. This is not surprising since IL-22 is known to be the key cytokine in mediating immune defense against extracellular bacterial pathogens (Liang et al 2006). The fact that poly(I:C) also induced IL-22 and IL-26 expression in spleen suggests that they may have some roles in host antiviral defense.…”
Section: Discussionmentioning
confidence: 97%